2005
DOI: 10.1016/j.ydbio.2005.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Bunched sets a boundary for Notch signaling to pattern anterior eggshell structures during Drosophila oogenesis

Abstract: Organized boundaries between different cell fates are critical in patterning and organogenesis. In some tissues, long-range signals position a boundary, and local Notch signaling maintains it. How Notch activity is restricted to boundary regions is not well understood. During Drosophila oogenesis, the long-range signals EGF and Dpp regulate expression of bunched (bun), which encodes a homolog of mammalian transcription factors TSC-22 and GILZ. Here, we show that bun establishes a boundary for Notch signaling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 97 publications
2
45
1
Order By: Relevance
“…In the Drosophila ovary, it was first shown to be required for maintaining follicle cells in their precursor stage and for specification of polar cells that mark the ends of the egg chamber (Grammont and Irvine, 2001;Larkin et al, 1996;Xu et al, 1992). During late oogenesis, N signaling is required for the switch from the mitotic cycle to the endocycle and differentiation of follicle cells by negatively regulating the cut gene (Shcherbata et al, 2004;Sun and Deng, 2005), and it is also required for patterning the anterior egg shell (Dobens et al, 2005). In this study, we have shown, for the first time to our knowledge, that N signaling is necessary and sufficient for controlling formation of the GSC niche.…”
Section: Introductionmentioning
confidence: 55%
“…In the Drosophila ovary, it was first shown to be required for maintaining follicle cells in their precursor stage and for specification of polar cells that mark the ends of the egg chamber (Grammont and Irvine, 2001;Larkin et al, 1996;Xu et al, 1992). During late oogenesis, N signaling is required for the switch from the mitotic cycle to the endocycle and differentiation of follicle cells by negatively regulating the cut gene (Shcherbata et al, 2004;Sun and Deng, 2005), and it is also required for patterning the anterior egg shell (Dobens et al, 2005). In this study, we have shown, for the first time to our knowledge, that N signaling is necessary and sufficient for controlling formation of the GSC niche.…”
Section: Introductionmentioning
confidence: 55%
“…Notch activation is strongly detected in larval terminal filament and cap cells and is also detected in adult cap cells (17,18). We examined Notch signaling in dinr mutants using the E(spl)m␤-CD2 reporter (17,19) (Fig. 5A-F).…”
Section: Resultsmentioning
confidence: 99%
“…hh-lacZ, a transgene carrying the hedgehog promoter upstream of the bacterial lacZ gene, was used to label terminal filament and cap cells (33). The tubulin-GPH (15), Dad-LacZ (24), and E(spl)m␤-CD2 (17,19) reporters were used to monitor insulin, BMP, and Notch signaling, respectively. The hsflipase (FLP) strain and other genetic elements used are described in Flybase (http://flybase.bio.indiana.edu).…”
Section: Methodsmentioning
confidence: 99%
“…36). These alleles provided a unique opportunity to investigate the function of TDB large isoforms in the follicular epithelium, where we know the most about bun functions (23,24). Expression of the large A isoform alone rescues null and heteroallelic mutations, suggesting that the small isoforms may be dispensable (36).…”
Section: Resultsmentioning
confidence: 99%
“…We have studied bun function in the follicular epithelium that overlies each maturing oocyte. Here, bun prevents epithelial cells from being recruited to a migratory fate (23); the boundary between epithelial and migrating cells is regulated through EGF and BMP regulation of bun expression (24). Expression of vertebrate TSC22D1 is similarly up-regulated by receptor tyrosine kinase signaling and down-regulated by BMP signaling during initiation of feather bud outgrowth in chicken skin (25).…”
mentioning
confidence: 99%